Integrated approaches to poverty problems - Salamova Ayna; Kantemirova Mira; Makazieva Zara (E3S Web of Conferences, 2023)
Poverty is a multifaceted issue that requires comprehensive strategies to tackle its various dimensions. By combining economic, social, and policy interventions, it becomes possible to address the root causes of poverty and work towards sustainable solutions. This abstract highlights the importance of understanding the complexities of poverty and the need for collaborative efforts among governments, organizations, and communities to create lasting change. Integrated approaches provide a holistic framework to combat poverty and improve the well-being of affected populations.